THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING HISTORY AND THE INCIDENCE OF STUNTING AMONG CHILDREN AGED 0–24 MONTHS AT JOHAR BARU DISTRICT PRIMARY HEALTH CENTER, INDONESIA - Dyah Woro Kartiko Kusumo Wardani; Crisilya Sapulette; Kusuma Dini; Ni Nyoman Sri Artina Dewi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study was conducted to examine the association between exclusive breastfeeding history and stunting among children aged 0–24 months at the Johar Baru District Primary Health Center. A correlational study design with a cross-sectional approach was employed. The study involved 83 mothers with children aged 0–24 months, who were selected through random sampling. Data were obtained via structured interviews using a master table and subsequently analyzed using the chi-square test with a significance level set at 5%. The findings indicated that the majority of mothers were between 20 and 35 years of age (81.9%), did not have paid employment (68.9%), and had attained secondary to higher levels of education (78.3%). More than half of the respondents reported providing exclusive breastfeeding (56.6%), and most children were classified as not stunted (75.9%). Bivariate analysis revealed a statistically significant association between maternal age and the occurrence of stunting (p = 0.039). However, no significant associations were identified between maternal occupation (p = 0.159), maternal educational attainment (p = 0.203), or exclusive breastfeeding history (p = 0.925) and stunting incidence. The study concludes that stunting is influenced by multiple interrelated factors, indicating that its prevention cannot rely solely on exclusive breastfeeding. Comprehensive strategies involving sustained nutritional interventions, improved environmental sanitation, and appropriate caregiving practices are essential to effectively reduce stunting. Therefore, health professionals are encouraged to continue promoting exclusive breastfeeding while simultaneously addressing other contributing factors that support optimal child growth and development.